Economic Dispatch of generator with valve point loading effect using immune evolutionary programming - Syamimi Hazuwin Mohamad (2023)
This thesis is documentaion prove of the author, of what has been gained and achieved through the final year project. The major objective of this thesis is to minimizing the total cost generation of the economic dispatch and the scope of this thesis are besed on the reseach project.